Analysis of The Effect of Audit Opinion, Size of Public Accounting Firm and Audit Delay on Stock Prices of Companies Listed in Lq45 on The Indonesian Stock Exchange - Dessy Yustiani (NAROTAMA UNIVERSITY, Indonesia, 2023)
The purpose of this study was to determine whether audit opinion, size of public accounting firm and audit delay affect stock prices in companies included in the LQ45 index on the Indonesia Stock Exchange (IDX) for the period 2017 to 2021. Design/methodology/approach: Multiple linear regression analysis. The research results are: 1) Audit opinion has a significant effect on the company's stock price enlisted in LQ45 index of IDX. 2) The size of public accounting firm has a significant effect on stock prices the company's stock price enlisted in LQ45 index of IDX. 3) Audit Delay has a significant effect on stock prices company's stock price enlisted in LQ45 index of IDX. 4) Audit opinion, size of public accounting firm and audit delay simultaneously has a significant effect on stock prices the company's stock price enlisted in LQ45 index of IDX. State your limitation here. This paper is original. Research Paper